Proses Komunikasi Interpersonal Orang Tua dalam Menanamkan Nilai Moral Pada Anak di Era Digital - Utami, Faiqotul Isma Dwi; Ardian, Randi (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2023)
The rapid expansion of digital technology has significantly transformed family communication patterns and posed new challenges to the moral development of children. Parents are required not only to supervise digital media usage but also to engage in effective interpersonal communication to instill moral values in the digital era. This study aims to examine the processes of parental interpersonal communication in cultivating moral values among children amid increasing digital exposure. Employing a qualitative descriptive approach, the research was conducted through in-depth interviews, observations, and document analysis involving parents of school-aged children in urban Indonesia. The findings reveal that parental communication in moral education occurs through dialogic interaction, emotional closeness, value negotiation, and behavioral modeling. Openness, empathy, consistency, and positive reinforcement emerge as key components of effective moral communication. However, challenges such as time constraints, technoference, and excessive gadget use often hinder communication quality. The study further demonstrates that moral education in the digital era requires adaptive communication strategies that integrate traditional values with digital literacy and ethical awareness. This research contributes theoretically by reinforcing negotiated morality theory and practically by providing guidance for parents and educators in strengthening moral communication within families. The findings suggest that sustained interpersonal communication is essential for nurturing children’s moral character in an increasingly digitalized environment.